The Relationship of Verbal Abuse of Parents to the Level of Adolescent Confidence in the Sei Gelugur People's Private Junior High School - Simorangkir, Lindawati; Saragih, Helinida; Olabertua Cici Winarsih Sinurat (Jurnal Midwifery, 2025)
Background Confidence is the foundation that every person or child must have to meet various types of needs in life. Lack of confidence in adolescents will have repercussions such as anxiety, pessimism, shame, fear of making mistakes, and lack of social integration. Verbal abuse from parents can have a huge impact on adolescents' confidence levels. When parents often use harsh words, excessive criticism, or condescending, teens can feel unappreciated and worthless. Method The following study method aims to identify the correlation between parental verbal abuse and adolescent confidence in Sei Gelugur Private Junior High School in 2024. Using the correlation method on the cross-sectional method. The population was 181 respondents. The technique in determining the sample is randome sampling, the number of samples is 123 respondents. Result The univariant analysis in this study explains the characteristics of the research variables. The results of the study proved that the majority of adolescents' confidence was in low characteristics of 54 people (43.9). As well as the category of Verbal Abuse was high as many as 56 people (45.5%). Conclusion The acquisition of statistical and chi-square tests showed a score of p=0.007 which means that there is a significant difference between Verbal Abuse of Parents and Adolescent Confidence at Sei Gelugur Private Junior High School in 2024. It is hoped that the following study can be used as a reference to increase information related to Parental Verbal Abuse on Adolescent Confidence.